Teaching efficacy of undergraduate PE students; what are the key predictors and what can PE educators learn from this? - Magill, Ceriann; Cronin, Colum; Walsh, Barbara; Polman, Remco; Rudd, James (Frontiers in Education, 2023)
Teaching efficacy describes the belief in a teacher’s ability to promote learning and this belief is an invaluable asset for all teachers. This study examined the contextual influences that predict PE teaching efficacy of first year undergraduate PE students wishing to progress into initial teacher training programmes. Using a mixed methods study design, 168 PE students completed an online questionnaire and sixteen of these participants took part in semi-structured focus groups. The data collection procedures investigated students’ perceived teaching efficacy and examined students’ awareness of how their involvements in PE or Sport have influenced their decision to study PE. Teaching experiences and role model influences were the key predictors of students perceived PE teaching efficacy. We recommend that higher education PE programmes should facilitate theoretically informed reflective learning opportunities to enable students to understand and make sense of the impact of these key predictors. These opportunities will enable students to make sense of their PE teaching efficacy starting point and identify efficacy development requirements. The study extends existing literature by identifying the key predictors of PE teaching efficacy derived from the acculturation experiences of undergraduate PE students.